Syntactic development in a Malay-English bilingual child: testing the prominence hypothesis and the lexical mapping hypothesis. - Mohamed Salleh, Rabiah Tul Adawiyah; Kawaguchi, Satomi; Di Biase, Bruno (2018)
Processability Theory (Pienemann, 1998, 2005) was originally developed to predict second language learners morphological and syntactic development over a single hierarchy. Further work on L2 syntax proposed extending the theory to include the Unmarked Alignment hypothesis, the Topic hypothesis and the Lexical Mapping hypothesis (Pienemann, Di Biase & Kawaguchi, 2005) assuming that learners begin with the least marked syntactic forms and proceed towards more marked structures. Recently, Bettoni and Di Biase (2015) propose to unify the Unmarked alignment hypothesis and the Topic hypothesis, replacing them with a single Prominence Hypothesis and proposed some minor adjustment for the Lexical Mapping hypothesis. This study analyses a bilingual Malay-English child’s syntactic development from the Prominence hypothesis and Lexical mapping hypothesis perspectives. The child was recorded in separate English and Malay contexts from age 2:10 until 4:8. Findings show that for the Prominence Hypothesis, the child begins with a canonical word order in both languages before proceeding to more marked sentence structures. For the Lexical Mapping hypothesis, the child also begins with the default thematic mapping before proceeding to nondefault mapping. These new PT hypotheses are tested for the first time in Malay-English bilingual development.